Mangiferin content in different parts of mango tree (Mangifera indica L.) in Thailand - Ngampuk Tayana (2019)
© 2019, Prince of Songkla University. All rights reserved. Mangiferin is a xanthone glucoside that possesses a broad range of therapeutic uses and has no reports of adverse effects. It is abundant in the leaves and stems of the mango tree (Mangifera indica L.). In order to evaluate and standardize plant raw materials containing mangiferin and their extracts, the high-performance liquid chromatography analytical method was developed to analyze mangiferin content in M. indica extracts. Separation was carried out on a Hypersil BDS C-18 column using 0.5% acetic acid in water and methanol (75:25, v/v) as the mobile phase. Various extracting solvents were employed to optimize the mangiferin yield from the M. indica leaves using sonication. The results showed that 70% methanol in water was the optimal solvent for mangiferin extraction. Mangiferin quantification in various parts of the M. indica collected from different locations of Thailand was performed. Our results indicated the optimal solvent, part, and stage of M. indica raw materials for further development.